Planning of Distribution Systems Using Mixed-Integer Linear Programming Models Considering Network Reliability - de Souza, João; Rider, Marcos J.; Mantovani, José Roberto Sanches (Journal of control, automation & electrical systems, 2015)
In this paper, a two-stage solution methodology for distribution network planning considering reliability indices improvement is proposed. This methodology comprises optimal distribution network expansion and improves network reliability by allocating sectionalizing switches and interconnection circuits (tie line circuits). The optimal expansion problem of radial aerial distribution systems is formulated as a mixed binary linear programming (MILP) problem aiming to reduce the investment and operational costs, subject to physical and operational constraints. The allocation of controlled sectionalizing switches and interconnection circuits is also formulated as a MILP in order to improve the network reliability indices. A pseudo-dynamic planning method is used to solve planning and reliability models through a heuristic technique that first solves the planning model followed by the solution of the reliability model, in each stage of planning horizon. Numerical results are presented for a 54-bus distribution system from literature.